2007
DOI: 10.1029/2006wr005346
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty assessment in watershed‐scale water quality modeling and management: 2. Management objectives constrained analysis of uncertainty (MOCAU)

Abstract: [1] Watershed-scale water quality models are increasingly used to support management decision making. However, significant uncertainty in model output remains an unaddressed issue. In our first study, a framework for assessing the uncertainty in watershed modeling and management was developed, and the application of the generalized likelihood uncertainty estimation (GLUE) approach was examined. The influence of subjective choices (especially the likelihood measure) in a GLUE analysis, as well as of availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 23 publications
(36 reference statements)
0
28
0
Order By: Relevance
“…We recommend that approaches for assimilating different types of information (models and monitoring data) are developed (Wikle and Berliner, 2007;Reichle, 2008), in order to harness the strengths of both approaches, to quantify the uncertainty in both simultaneously, and ultimately to provide an even stronger scientific basis for estimating and reporting river pollutant loads with estimates of uncertainty (Romanowicz et al, 2006). Representing all such sources of uncertainty (parameter, model and data) in deterministic models, for example by employing Bayesian techniques (Zheng and Keller, 2007), would enable transparent, objective and repeatable comparisons with other load estimates, but is not a trivial task for models like SedNet due to the number of model inputs.…”
Section: Comparing Deterministic and Statistical Modelsmentioning
confidence: 98%
“…We recommend that approaches for assimilating different types of information (models and monitoring data) are developed (Wikle and Berliner, 2007;Reichle, 2008), in order to harness the strengths of both approaches, to quantify the uncertainty in both simultaneously, and ultimately to provide an even stronger scientific basis for estimating and reporting river pollutant loads with estimates of uncertainty (Romanowicz et al, 2006). Representing all such sources of uncertainty (parameter, model and data) in deterministic models, for example by employing Bayesian techniques (Zheng and Keller, 2007), would enable transparent, objective and repeatable comparisons with other load estimates, but is not a trivial task for models like SedNet due to the number of model inputs.…”
Section: Comparing Deterministic and Statistical Modelsmentioning
confidence: 98%
“…In Zheng and Keller [2007b], we showed that for diazinon in a southern California watershed, a simple model adequately represented the observational error:…”
Section: Mocau Analysismentioning
confidence: 98%
“…However, the study did not evaluate GLUE's performance from a [Zheng and Keller, 2007a]. We therefore developed an approach, Management Objectives Constrained Analysis of Uncertainty (MOCAU), tailored specifically for management-oriented watershed modeling [Zheng and Keller, 2007b]. MOCAU inherits GLUE's equifinality ideology, while explicitly considering management objectives and observational uncertainty.…”
Section: A New Bayesian Approach For Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For different management objectives, different sets of random parameters may need to be considered in the UA. Eventually, the UA has to be management-oriented, as suggested by Zheng and Keller (2007b). Nevertheless, how to determine an appropriate set of random parameters for the MCMC UA deserves a separate study.…”
Section: Number Of Random Parametersmentioning
confidence: 99%